Spectroscopic (IR and Raman) studies of hydrogen bonding in selected organic compounds containing the carbonyl or phosphoryl group - Heyns, A.M. (University of Pretoria, 2022)
Dissertation (MSc (Physical Chemistry))--University of Pretoria, 1994.